Work teachers guiding of training in courses of teacher education - Nadiane Feldkercher (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The stage curriculum in teacher education aims to bring the trainee primary school, their future field. It is activities supervised by entail monitoring and guidance of the teacher training adviser (linked to the university) and the classroom teacher's class (linked to the basic school). In this study we aimed to identify and analyze the work done by academics to guide the stage of a training course for teachers of mathematics at a public university in southern Brazil. We use the interview as an instrument of data collection along with two faculty advisers' internship. Analyzes were guided by legal guidelines on the stage and authors such as Pimenta and Lima (2004), Pimenta (2006), Zabalza (2004) and Zeichner (2009). Among the results, we point out that the demand for labor of guiding is broad and often, these teachers do not have the minimum requirements to monitor and supervise the interns. The mismatch between the school calendar and timetable university was a limitation identified in the development stage of this course. We realized the need for a closer relationship between school and university and review of what refers to cooperative work between the two faculty advisers internship this course.